P–645 Abnormal thyroid hormone levels are associated with biochemical primary ovarian insufficiency and low ovarian reserve: a cross-sectional study. (6th August 2021) - Feng, C
Abstract: Study question: To address whether there was a correlation between thyroid parameters and primary ovarian insufficiency. Summary answer: Thyroid dysfunction was related with bPOI and LOR. What is known already: In our daily clinical work, there seems to be a link between thyroid disease and POI. A recent study reported that subclinical hypothyroidism was associated with lower ovarian reserve during later reproductive age. Animal studies demonstrated that thyroid hormones played important roles in ovarian functions, and both maternal hypothyroidism and hyperthyroidism were related with reduced primordial, primary and secondary follicle number in rats. However, others reported that thyroid autoimmunity (TAI) and hypothyroidism were not associated with DOR. In all, accumulative animal and epidemiological studies indicated the connection between thyroid function and ovarian reserve, but the results were still inconsistent. Study design, size, duration: This is a cross-sectional study with consecutive women performed ovarian reserve assessment and thyroid test in the Second Hospital of Zhejiang University School of Medicine from April 2016 to March 2019. A total of 2109 women were included, with 111 with bPOI and 1771 without bPOI. To exclude the influence of age the participants were categorized into low ovarian reserve (LOR) and non-LOR groups based on age-specific AMH, including 78 LOR and 2031 non-LOR. Participants/materials, setting, methods: At the outpatient, a doctor carried out an interview, recorded age, body mass index (BMI), past history, and current treatment, and made a diagnosis. Serum AMH, FSH, TPOAb, TgAb, Tg, TT3, FT3, TT4, FT4, and TSH levels were measured with electrochemiluminescence method. Main results and the role of chance: TT3, FT3, FT4 was significantly positively correlated with serum AMH level. Further logistic regression analysis found that abnormal TT3, FT3 and TT4 levels were related to increased risks of bPOI and LOR. Chi-square analysis also proved that the incidence of abnormal TT3, FT3 and TT4 increased significantly in women with bPOI or LOR. The incidence of bPOI and LOR increased significantly in women with 2 or 3 abnormal thyroid hormones. The above analyses demonstrate in multiple aspects that thyroid dysfunction is related with decreased ovarian reserve. Limitations, reasons for caution: Since this is a retrospective cross-sectional study, we only got the correlation between factors, and we could not achieve causal relationship. Further prospective cohort or randomized controlled trial (RCT) studies are required to make the results more robust. Wider implications of the findings: The present study demonstrated that thyroid dysfunction was related with bPOI and LOR. It might be thyroid hormones, not TSH or thyroid antibodies, played the major role in ovarian reserve impairment. The treatment of euthyroxine may improve the ovarian reserve function. Trial registration number: Not applicable